Answer: a) y = f(x - 6)
b) y = f(x) - 2
<u>Step-by-step explanation:</u>
For transformations we use the following formula: y = a f(x - h) + k
- a = vertical stretch
- h = horizontal shift (positive = right, negative = left)
- k = vertical stretch (positive = up, negative = down)
a) f(x) has a vertex at (-1, 1)
M has a vertex at (5, 1)
The vertex shifted 6 units to the right → h = +6
Input h = +6 into the equation and disregard "a" and "k" since those didn't change. ⇒ y = f(x - 6)
b) f(x) has a vertex at (-1, 1)
N has a vertex at (-1, -1)
The vertex shifted down 2 units → k = -2
Input k = -2 into the equation and disregard "a" and "h" since those didn't change. ⇒ y = f(x) - 2
The volume is (area of cross-section) x (length) .
-- The cross-section is a triangle. The area of a triangle is
Area = (1/2) (base) (height) .
In this one, the base is 9/4 m and the height is 3-1/3 m .
Area = (1/2) (9/4 m) (3-1/3 m)
Area = (1/2) (9/4) (10/3)
Area = 90/24 m² .
-- Volume = (area of cross-section) x (length)
Volume = (90/24 m²) x (7-1/3 m)
Volume = (90/24) x (22/3) m³
Volume = (1,980 / 72) m³
<em>Volume = 27.5 m³ </em>
Answer:
6
Step-by-step explanation:
Answer:
y - 6 = -8(x - 6)
Step-by-step explanation:
point-slope form is y-y₁=m(x-x₁)
we have slope=-8 and also this point (6,6) so
y - 6 = -8(x - 6)
hope this helps you